Memória e identidade dos protagonistas em Estorvo e Benjamim - Rossetto, Simone Maria (2014)
This research proposes to make a reading of two novels by Chico Buarque, Estorvo and Benjamin. To do so, we analyze four categories: the narrator, and society, with greater emphasis, memory and identity. The work was based on studies of Joël Candau, in Memory and Identity (2012); Guy Debord, in The Society of the Spectacle (2003), Maurice Halbwachs, in Collective Memory (2003), Stuart Hall, in Cultural identity of post-modernity (1992), among others. The main objective is to investigate how the memory of the protagonists of Estorvo and Benjamin helps in the recognition of self, their identity process. At the end of the survey, it was realized that the memories of the central characters are equally as their identities, fragmented and unable to form a complete picture of being. In line with modern society, the protagonists are individuals disoriented and lonely